Caracterização dos óbitos de médicos veterinários e zootecnistas no Brasil entre 2006-2012 - Talline Aredes Hang Costa (2015)
Mortality indicators are the tool most often used to evaluate the health situation and the dynamics of diseases and disorders that affect a given population. The overall objective of this study was to characterize the deaths of veterinarians and animal scientists occurred in Brazil between 2006-2012. Cross-sectional analysis of mortality data from the Mortality Information System (SIM) of death records reported in Brazil between 2006-2012. Socio-demographic variables were selected and related to deaths for descriptive analysis and for analysis of the proportional mortality rates. The combination of the frequencies of the variables was measured by Pearsons chi-squared test and Fishers exact test with a P-value of 0.05. The results correspond to n=950 death certificates. Excluded n=185 in compliance with the eligibility criteria, totaling n=765 death certificates. Veterinarians accounted for 92.29% of the total and animal scientists accounted for 7.71%. All death certificates specified the underlying cause of death, and 2.48% were coded as ill-defined (R95-R99). The deceased were mostly: male (84.31%), white race/color (83.14%), married (57.91%) and death occurred age ranged from 22 to 100 years. Regarding the causes, neoplasms were the leading causes of death (considering the total number of cases) among veterinarians and animal scientists (26,27%), followed by diseases of the circulatory system (23.66%) and external causes (22.35%). On the other hand, the proportional mortality, analyzed by sex, showed differences in the leading causes of death of veterinarians and animal scientists, as well as by age group. Workplace accidents were responsible for 13 deaths, which is less than 2% of all deaths. Noteworthy is the wide underreporting of work accidents. The results need to be seen in the light of these limitations and reveal challenges to be overcome to improve living conditions, health and work of veterinarians and animal scientists. The differences regarding the cause of death and proportional mortality rates require the adoption of specific preventive measures and targeted for each occupational group. The highlights: the average age of death of professionals with significant differentiation between veterinarians and animal scientists and between the sexes; the challenge to understanding the relationship between age and cause of death in the analysis of proportional mortality and the identification of a distinct profile of early death from causes related to occupation. Deaths of veterinarians and animal scientists from external causes contribute to the national discussion of violence prevention and cessation of deaths from preventable causes. SIM, with the well known increase of its scope, faces challenges to improve the quality of its data mainly due to inadequate completion of death certificates, but still proved to be a valuable and quality tool for this study.